Exploring how Health-related Quality of Life (HRQOL) is experienced among patients living with HIV associated TB in Khayelitsha, South Africa - Hickman, John-Henry (Department of Public Health and Family Medicine, 2020)
Health-related quality of life (HRQOL) is a construct that has received attention in research for nearly four decades. However, renewed interest in this field came about with advances in medical technology and health policies. Better treatment options and policies, which enables greater access to health care, have improved health outcomes, such as leading to an extension in life expectancy. This rings particularly true for Human Immunodeficiency virus (HIV) and associated illnesses such Tuberculosis (TB). However, improvements in health outcomes are not necessarily accompanied by satisfactory patient experiences of HRQOL. Health-related quality of life is predominantly studied through quantitative research methodologies. However, the measures used are not entirely tailored to the South African context. Consequently, this mini-dissertation aims to explore HRQOL using qualitative methodological inquiry within the South African context. This mini dissertation is structured around the three following components: A research protocol (Part A) which addresses HRQOL in a South African context with particular focus on HIV and TB. Part B is a literature review examining existing HIV, TB and HRQOL literature, with emphasis on the South African context. The final section (Part C) is a manuscript for a journal article prepared to be published. Part C focuses on the social experience of HRQOL and how it is the central construct to experiencing HRQOL in South Africa as opposed to an individualised view in Western settings. The findings from this mini dissertation can add to the limited existing HRQOL literature in South Africa, by providing a perspective on how HRQOL is experienced in this country. The knowledge obtained here can further aid in the development or improvement of interventions and policies which aim to not only improve patient health outcomes, but HRQOL as well. Lastly, it can provide valuable information to those focused on developing quantitative HRQOL tools that are appropriate for use in South Africa.